Simultaneous determination of cyclophosphamide and carboxyethylphosphoramide mustard in human plasma using online extraction and electrospray tandem mass spectrometry (HTLC-ESI-MS/MS) - Bai, Feng (2009)
A rapid and selective method for simultaneous determination of cyclophosphamide and its metabolite carboxyethylphosphoramide mustard (CEPM) was developed using online sample preparation and separation with tandem mass spectrometric detection. Diluted plasma was injected onto an extraction column (Cyclone MAX 0.5 mm × 50 mm, >30 μm), the sample matrix was washed with an aqueous solution, and retained analytes were transferred to an analytical column (Gemini 3 μm C18 110A, 100 mm × 2.0 mm) using a gradient mobile phase prior to detection by MS/MS. Analytes were detected in an API-3000 LC-MS/MS system using positive multiple-reaction monitoring mode (m/z 261/140 and 293/221 for CTX and CEPM, respectively). Online extraction recoveries were 76% and 72% for cyclophosphamide and CEPM. Within-day and between-day variabilities were <3.0%, and accuracies were between -6.9% and 5.2%. This method has been used to measure plasma cyclophosphamide and CEPM concentrations in an ongoing Phase II study in children with newly diagnosed medulloblastoma.